IV Workshop on Computational Data Analysis and Numerical Methods - Grilo, Luis M. (2017)
The IV Workshop on Computational Data Analysis and Numerical Methods (WCDANM) is going to be held on October 27, 2017, at the Beja Polytechnic Institute and is a unique opportunity to disseminate scientific research related to the areas of Mathematics in general and in particular in the areas of Statistics and Numerical Analysis in the theoretical and/or practical field, using new techniques, giving especial emphasis to applications in Medicine, Biology, Biotechnology, Engineering, Industry, Environmental Sciences, Finance, Insurance, Management and Administration. The meeting will provide a forum for discussion and debate of ideas of interest to the scientific community in general, and will be attended by speakers with relevant publications in international journals. With this meeting it is expected new scientific collaborations among colleagues, namely new collaborations in Masters and PhD projects. The event is open to the entire scientific community (with or without communication/poster) and without registration fees. It is worth mentioning that this meeting will take place in its 4th edition, with previous editions taking place at the Polytechnic Institute of Tomar (2014), the University of Évora (2015) and the Polytechnic Institute of Portalegre (2016).